Synthesis, characterization, and functionalization of zirconium tungstate (ZrW2O8) nano‐rods for advanced polymer nanocomposites - Kumar, Vijay; Li, Yuzhan; Wu, Hongchao; Kessler, Michael R. (Wiley, 2017)
Nanomaterials based on zirconium tungstate (ZrW2O8) exhibit numerous outstanding properties that make them ideal candidates for the development of high-performance composites. Low coefficient of thermal expansion for advanced materials is a promising direction in the field of insulating nanocomposites. However, the agglomeration of zirconium tungstate (ZrW2O8)-based nanomaterials in the polymer matrix is a limiting factor in their successful applications, and studies on surface functionalization ZrW2O8 for advanced nanocomposites are very limited. In this work, ZrW2O8 nano-rods were synthesized using a hydrothermal method and subsequently functionalized in a solvent-free aqueous medium using dopamine. Both pristine and functionalized nano-rods were thoroughly characterized using Fourier transform infrared spectroscopy, Raman spectroscopy, thermogravimetric analysis, X-ray diffraction, Scanning Electron Microscopy (SEM), and transmission electron microscopy techniques, which confirmed the successful functionalization of the nanomaterials. Polymer nanocomposites were also prepared using epoxy resin as a model matrix. Polymer nanocomposites with functionalized ZrW2O8 nano-rods exhibited low coefficient of thermal expansion and enhanced tensile properties. The improved properties of the nanocomposites render them suitable for electronic applications.
Keywords: 10.1002/pat.4014; negative CTE; thermosetting resins; polymer matrix nanocomposites; mechanical properties